Formative Assessment Practices in Online Learning for Assessing Students’ Writing Competence - Pradnyadewi, Diah Ayu Manik; Dewi, Ni Luh Putu Eka Sulistia; Era Marsakawati, Ni Putu; Yudha Paramartha, A.A Gede (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
Writing is considered as one of the essential language competences which should be mastered by the students because it is highly valued in the academic context. As a result, the teachers have to conduct assessment in helping students to improve their writing competence. One of the assessment types which can be implemented by the teachers is formative assessment. Formative assessment is a process which is continuously conducted by the teachers to collect learning evidences of the students as an input to improve their’ learning and improve the quality of learning instructions. However, due to the emergence of Covid-19 Pandemic, the process of formative assessment for assessing students’ writing competence should be conducted in online learning. The phenomena of the formative assessment for assessing students’ writing competence in online learning existed in the junior high school English teachers at SMPN 3 Denpasar. This study aimed at analyzing the planning and implementation of formative assessment for assessing students’ writing competence in online learning. The design of this study was qualitative study particularly case study. The data were obtained by conducting document analysis, survey, and interview. The result of the study showed that the teachers planned and implemented 5 kinds of formative assessment namely self-assessment, peer-assessment, teacher-feedback, sharing an understanding of assessment goals, and varied formative assessment.